Analisis Kuat Tekan Beton dengan Variasi Kekangan Carbon Fiber Wrap - IMMANUEL PANUSUNAN TUA PANGGABEAN (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2020)
The use of Carbon Fiber Wrap, continues to increase along with increasing research on the ability of this type of material to provide restraints that can increase the ability to bear the burden given. Carbon Fiber Wrap used has a standard use of unidirectional fiber, which is the use of unidirectional fibers. The study used concrete material using 20 (twenty) samples aimed at finding out how much influence the implementation did not follow the standards and conditions for using Carbon Fiber Wrap. Tests carried out using cylindrical specimens with a diameter of 10 cm and height of 20 cm. As comparison, 5 (five) test specimens were not installed with Carbon Fiber. The test results obtained from 5 (five) specimens using epoxy chemical before and after installation of Carbon Fiber on the specimens with unidirectional fibers add concrete compressive strength by an average of 56%. As many as 5 (five) specimens using chemical epoxy before installing Carbon Fiber on the specimens with unidirectional fibers, increased the compressive strength of concrete by an average of 26%. And as many as 5 (five) specimens using epoxy chemical before and after the installation of Carbon Fiber in the opposite direction of the perpendicular fiber the fiber adds an average compressive strength of only 18%. Other observations from this study were obtained on the difference in collapse of specimens mounted with Carbon Fiber Wrap as a result of specimens which were not fitted with Carbon Fiber Wrap. The collapse does not form a shear or normal failure pattern on the test object but the concrete of the test object is destroyed by damaging and tearing the Carbon Fiber Wrap.